2021
DOI: 10.1108/ijppm-10-2020-0567
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating challenges of small social enterprises to improve performance

Abstract: PurposeSmall social enterprises (SEs) face many challenges as they seek to secure their survival, sustainability and performance, but little is known about the interrelations among these challenges and how these SEs might mitigate their challenges by using online platforms.Design/methodology/approachDrawing on the results of 19 in-depth semi-structured interviews with founders of small SEs in Australia, the authors present two integrative frameworks: one demonstrates how different challenges directly or indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Typically, investors and government bodies invest based on traditional market principles that emphasize financial reporting, with high revenues serving as a means of legitimizing the enterprise. In contrast, society expects to see social impact demonstrated through social reporting (Abedin et al, 2021). Bradford et al (2020) investigated accountability priorities in Australia and found that financial accountability was generally considered more important due to the need for financial sustainability to effectively pursue social goals.…”
Section: Theme 1: Acquiring Tangible Resources-financial and Material...mentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, investors and government bodies invest based on traditional market principles that emphasize financial reporting, with high revenues serving as a means of legitimizing the enterprise. In contrast, society expects to see social impact demonstrated through social reporting (Abedin et al, 2021). Bradford et al (2020) investigated accountability priorities in Australia and found that financial accountability was generally considered more important due to the need for financial sustainability to effectively pursue social goals.…”
Section: Theme 1: Acquiring Tangible Resources-financial and Material...mentioning
confidence: 99%
“…Typically, investors and government bodies invest based on traditional market principles that emphasize financial reporting , with high revenues serving as a means of legitimizing the enterprise. In contrast, society expects to see social impact demonstrated through social reporting (Abedin et al., 2021). Bradford et al.…”
Section: Findings and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some studies indicate a skepticism on the use of traditional PM systems depending on the organization structure (Moxham, 2009;Straub et al, 2010;Moura et al, 2019Moura et al, , 2020, e.g. on projects and institutional planning (Moura, 2018) or different organizational structures (Abedin et al, 2021;Wang et al, 2021;Martins et al, 2021). Also, the industry 4.0 era represents a challenge to adopt some PM systems.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019, 2020), e.g. on projects and institutional planning (Moura, 2018) or different organizational structures (Abedin et al. , 2021; Wang et al.…”
Section: Introductionmentioning
confidence: 99%